Education for Meaning: What Is It and Why Do We Need It? - Karmon, Amnon (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2021)
The central assertion of the article is that the most important mission in the field of education today is to design a new, comprehensive educational concept for schools, without with schools are consigned to an “educational-pedagogical vacuum” that advances extraneous and alienating purposes. The analysis delineates the theoretical foundations and practical consequences of such a new concept called “Education for Meaning.” That concept addresses meaning in two senses: meaning as understanding the world and meaning as significance of and reason for living. The pattern of teaching and learning applied in the creative arts is presented as a pedagogical model upon which such an educational approach can be modeled. The article highlights the urgent educational need to initiate a dialogue that focuses on “big theories” of education in place of the prevailing educational discourse which has become superficial and crassly economy-focused.